Cardiovascular impact of COVID-19: an array of presentations: Cardiovascular impact of COVID-19 - Maab, Hira; Mustafa, Faryal; Shabbir, Syeda Javeria (Acta Biomedica Atenei Parmensis, 2021)
The novel coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) dominantly infects the lungs, causing interstitial pneumonitis and severe acute respiratory distress syndrome (ARDS) however the cardiovascular implications of the infection are particularly significant, especially in their contribution to disease morbidity and mortality. SARS-CoV-2 enters the cardiovascular system by binding to the angiotensin-converting enzyme 2 (ACE2) receptor. The pathogenic cardiovascular mechanism of the virus involves systemic inflammation via a cytokine storm and direct myocardial injury. The most frequently reported cardiovascular complications of COVID-19 include acute myocardial injury, myocarditis, myocardial infarction, heart failure, cardiomyopathy, arrhythmias, and venous thromboembolic events. Also, pre-existing cardiovascular disease in COVID-19 patients is a prime marker for attaining severe disease and is associated with high mortality rates.  Lastly, the medications under investigation for COVID-19 may have their individual cardiovascular adverse effects. We hereby present a concise literature review that summarizes recent peer-reviewed and pre-print articles published on the cardiovascular implications of COVID-19. The information on the subject is being updated frequently therefore latest literature needs to be added in newly published reports for a better understanding of the topic.